Engineering Technology Development in the Era of Industry 4.0: A Literature Review - Siti Nur Afiqah binti Ruslan (Journal Of Engineering And Technology Innovation ( JETI ), 2025)
The Fourth Industrial Revolution (Industry 4.0) has initiated a fundamental transformation in the field of engineering through the integration of advanced digital technologies such as cyber-physical systems (CPS), the Internet of Things (IoT), artificial intelligence (AI), and big data analytics. This study aims to examine the development of engineering technology in the Industry 4.0 era using a literature review approach. By analyzing relevant academic sources published between 2015 and 2025, the research identifies key technological trends, the impact on engineering education, the challenges of industrial adoption, and opportunities for sustainability and innovation.The results show that Industry 4.0 technologies have enhanced the adaptability, efficiency, and intelligence of engineering systems. However, their implementation poses significant challenges, including high costs, skills gaps, and cybersecurity risks. The study also highlights the need to reform engineering education to prepare a future-ready workforce equipped with interdisciplinary competencies. Ultimately, the findings underline the importance of collaboration among educational institutions, industry stakeholders, and policymakers to ensure the successful advancement of engineering in a digital and sustainable future.